STUDI INTELLECTUAL CAPITAL TERHADAP NILAI PASAR DAN KINERJA KEUANGAN PERUSAHAAN MAKANAN DAN MINUM (TERDAFTAR PADA BURSA EFEK INDONESIA TH.2009-2010) - Jaluanto Jaluanto (Serat Acitya, 2012)
This study aimed to examine the effect of intellectual capital on market value and financial performance of the company, especially in the food and beverage company listed on the Stock Exchange 2009-2010. By using a model-Value Added Intellectual pulic Coefficients (VAIC), this study examined the relationship between the efficiency of value added (VAIC) of the three major resource companies Human Capital (HC), Structural Capital (SC), Customer Capital (CC) of the Market Value company (MtBV) and Corporate Financial Performance (ROA). The data used are 12 companies listed in the Indonesia Stock Exchange in 2009-2010. Analysis of data using multiple recessions to measure the strength of relationship between two or more variables, and to show the direction of the relationship between the dependent variable with the independent variable. The dependent variable is assumed random / stochastic, which means it has a probabilistic distribution. The independent variable is assumed to have a fixed value (in repeated sampling). Results showed no effect of the variable is Intellectual Capital consists of VACA the Book to Market Value, while for variable VAHU and STVA have an influence on Book to Market Value, No effect between variables Intellectual Capital consists of VACA the Company's financial performance, while for variable VAHU and STVA have any impact on financial performance of the Company.